(Invited)Kinetic Models for the Degradation Mechanisms of PGM-Free ORR Catalysts. (19th June 2018) - Yin, Xi; Zelenay, Piotr
Abstract : Platinum group metal-free (PGM-free) catalysts, based on earth-abundant elements such as carbon, nitrogen, and transition metals, have shown promising oxygen reduction reaction (ORR) activity in fuel cells. Intensive research activities have focused on the improvement of activity and understanding of active sites in PGM-free catalysts. However, the durability of PGM-free catalysts in fuel cell cathode under realistic operating conditions has been addressed to a much lesser degree than the initial ORR activity, with only qualitative degradation mechanisms proposed to account for the generally fast activity loss in the fuel cell. Herein, we introduce to PGM-free ORR electrocatalysis a quantitative logistic decay model, based on a two-step autocatalytic degradation mechanism to portray catalyst degradation behavior. This model describes well the current-time data measured in the kinetic range of the fuel cell (fuel cell cathode) operation. The results further suggest that the formation of deactivation species during the ORR is responsible for the loss of catalytic active sites and ensuing cell performance loss.